An ultrasensitive sandwich-type electrochemical immunosensor based on functionalized mesoporous carbon for IgG detection. Issue 38 (29th March 2016) - Yang, Yuying; Liu, Qing; Liu, Yan; Li, Zhaohui; Li, Yueyun; Wang, Ping; Zhang, Daopeng; Zhao, Zengdian; Liu, Yuying; Dong, Yunhui
Abstract : Immunoglobulin (IgG) plays an important role in the accurate diagnosis of some diseases. Abstract : Immunoglobulin (IgG) plays an important role in the accurate diagnosis of some diseases. Conventional clinical detection is expensive and has low sensitivity. To overcome these disadvantages, in this study, a novel and ultrasensitive electrochemical immunosensor based on functionalized ordered mesoporous carbons (OMC) was developed. To this purpose, the mesoporous carbon was functionalized with 3-aminopropyl triethoxysilane to stabilize gold nanoparticles (Au NPs) for the efficient adsorption of chromium ions (Cr 3+ ) and secondary antibodies (Ab2 ). The prepared immunoassay is better than conventional label-free electrochemical immunoassays due to the synergetic effect provided by the Cr 3+ @Au@OMC. The prepared nanocomposites (Cr 3+ @Au@OMC) functioned as a signal magnification label, as it has superior electrocatalytic activity for hydrogen peroxide reduction. Meanwhile, Au NPs were electrodeposited on the electrode surface to increase the amount of primary antibodies (Ab1 ) being absorbed. Under the optimal conditions, a linear range was identified from 0.01 pg mL −1 to 100 ng mL −1 with a detection limit of 3.33 pg mL −1, comparing favorably with the conventional limit of 3 ng mL −1 . Thus, the developed immunosensor has great potential in clinical and diagnostic applications due to its high sensitivity, good selectivity and stability for the quantitative detection of IgG.